2018
DOI: 10.3390/jsan7010011
|View full text |Cite
|
Sign up to set email alerts
|

IoT-Based Intelligent Modeling of Smart Home Environment for Fire Prevention and Safety

Abstract: Fires usually occur in homes because of carelessness and changes in environmental conditions. They cause threats to the residential community and may result in human death and property damage. Consequently, house fires must be detected early to prevent these types of threats. The immediate notification of a fire is the most critical issue in domestic fire detection systems. Fire detection systems using wireless sensor networks sometimes do not detect a fire as a consequence of sensor failure. Wireless sensor n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
89
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 165 publications
(89 citation statements)
references
References 33 publications
0
89
0
Order By: Relevance
“…In [5] they designed a wireless sensor network for early detection of house fires. They simulated a fire in a smart home using the fire dynamics simulator and a language program.…”
Section: Smoke Detectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In [5] they designed a wireless sensor network for early detection of house fires. They simulated a fire in a smart home using the fire dynamics simulator and a language program.…”
Section: Smoke Detectorsmentioning
confidence: 99%
“…Jian Mao et al [4] enhance machine learning algorithms to play a role in the security in a smart home ecosystem. Faisal Saeed et al [5] propose using sensors to sense and provide in real-time, fire detection with high accuracy.…”
Section: Introductionmentioning
confidence: 99%
“…[21], a mobile rescue robot was employed to explore and monitor the nuclear accident at the Fukushima power plant; this study revealed that reliable communication between the operator and robot system is crucial to gather internal information. This means that interworking and communication with the previously mentioned IoT devices is important [22]. Kim et al [23] proposed a portable fire evacuation guide robot system; it gathers temperature, O 2 and CO gas information through wireless communication.…”
Section: Firefighting Robot Technologymentioning
confidence: 99%
“…For instance, the currently used Internet of Things, which works as a local network of objects such as Machine-to-Machine (M2M), Wireless Sensor Networks (WSNs), smart homes, etc., can only obtain information from a specific region [34,[38][39][40]. The IoT provides more comprehensive, large-scale, and antique information of the surrounding by collaborating a diverse intranet of things, even though the devices have heterogeneity, local communication protocols, device mobility in the clustering, and different deployment technologies [39,41,42].…”
Section: Related Workmentioning
confidence: 99%
“…IoT devices generate massive amounts of real-time data and information on the physical world, therefore, dealing with that real-time data in smart cities (i.e., public health care, transportation, fire sensors, etc.) [32][33][34] and dealing with high-speed big data are still very big challenges [35,36]. The SIoT system empowers the IoT devices to connect globally with each other to share information and services.…”
Section: Introductionmentioning
confidence: 99%